Chapter 6. Electrochemical Methods (Analytical Methods for Drug Development, 2025)
AuthorMr. Mushraff Ali Khan MAssociate Professor, Department of Pharmaceutics, Sultan-ul-Uloom College of Pharmacy, Banjara Hills, Hyderabad, Telangana, IndiaAbstractElectrochemical techniques analyze pharmaceutical compounds through electrical property measurements. Potentiometry measures potential differences between electrodes, enabling pH determination, ion-selective detection, and endpoint determination in pharmaceutical assays. Electrode selection, calibration procedures, and system suitability testing ensure accurate results. Voltammetry techniques including cyclic, differential pulse, and stripping methods quantify drug substances, detect impurities, and characterize redox behavior by measuring current-voltage relationships. Conductometry measures solution conductivity for titration endpoints, ion detection, and water purity assessment in pharmaceutical contexts. These electrochemical methods support drug stability assessment, dissolution media characterization, and manufacturing process monitoring with advantages in sensitivity, cost-effectiveness, and direct analysis capabilities. Electrochemical techniques provide complementary approaches for molecules with electroactive functional groups, offering alternatives to spectroscopic and chromatographic methods.Keywords: Potentiometry, Drug Analysis, Electroactive Pharmaceutical Compounds, Redox Behavior, Ion Detection Methods, ConductivityVIEW PDF